Implementasi Alat Peraga “Ikon-E” Merupakan Kunci Sukses Memahami Konfigurasi Elektron (Cara Pengisian Konfigurasi Elektron Sebagai Media Pembelajaran Inovatif di SMA) - Mulyawati, Tin; Purwanda, Eka (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to evaluate the effectiveness of using electron configuration content tools ("e-icons") as a learning medium at the Senior High School (SMA) level. Electron configuration is an important concept in chemistry and understanding it can improve students' understanding of class X atomic structure material. Research data will be collected through a knowledge test on the group of students who use the "e-ikon" tool, called the experimental group, and the group of students without using the "e-ikon" tool, called the control group. Also, through a questionnaire that assesses students' perceptions of the use of electron configuration content tools. Data analysis will be conducted to determine whether the use of the electron configuration content tool can improve students' understanding and help them better internalize the concept of electron configuration. The conclusion that can be drawn is that the scores of students from the experimental class group have a higher average score than the average scores of students from the control class group. This means that the "e-icon" tool has a real influence on students in understanding electron configurations. The time needed for teachers to explain is shorter with the help of the “e-icon” tool. Students become happier studying chemistry. Filling in the configuration using tools lasts a long time in the student's memory.